The in vitro antimicrobial activity of natural infant fluoride-free toothpastes on oral micro-organisms - Carvalho, Fabíola G.; Negrini, Thais de Cássia; Sacramento, Luis Victor S.; Hebling, Josimeri; Spolidorio, Denise M. P.; Duque, Cristiane (My University, 2011)
Purpose: The objective of this study was to evaluate the antimicrobial activity of six toothpastes for infants: 3 fluoride-free experimental toothpastes - cashew-based, mango-based and without plant extract and fluoride compared with 2 commercially fluoride-free toothpastes and 1 fluoridated toothpastes. Methods: Six toothpastes for infants were evaluated in this study: (1) experimental cashew-based toothpaste; (2) experimental mango-based toothpaste; (3) experimental toothpaste without plant extract and fluoride (negative control); (4) First Teeth brand toothpaste; (5) Weleda brand toothpaste; and (6) Tandy brand toothpaste (positive control). The antimicrobial activity was recorded against Streptococcus mutans, Streptococcus sobrinus, Lactobacillus acidophilus, and Candida albicans using the agar plate diffusion test. Results: First Teeth, Weleda, mango-based toothpaste, and toothpaste without plant extract presented no antimicrobial effect against any of the tested micro-organisms. Cashew toothpaste had antimicrobial activity against S mutans, S sobrinus, and L acidophilus, but it showed no antimicrobial activity against C albicans. There was no statistical difference between the inhibition halo of cashew and Tandy toothpastes against S mutans and L acidophilus. Conclusions: Cashew fluoride-free toothpaste had inhibitory activity against Streptococcus mutans and Lactobacillus acidophilus, and these results were similar to those obtained for fluoridated toothpaste.
Keywords: Anarcadium occidentale; Mangifera indica; Plant extracts; Toothpaste; fluoride sodium; plant extract; toothpaste; topical antiinfective agent; Anacardium; analysis of variance; Candida albicans; comparative study; drug effect; human; in vitro study; infant; Lactobacillus acidophilus; Mangifera; microbial sensitivity test; Streptococcus mutans; Streptococcus sobrinus; Analysis of Variance; Anti-Infective Agents, Local; Humans; Infant; Microbial Sensitivity Tests; Plant Extracts; Sodium Fluoride; Toothpastes